Challenges in managing Pseudomonas aeruginosa in non-cystic fibrosis bronchiectasis. (August 2016) - Wilson, Robert; Aksamit, Timothy; Aliberti, Stefano; De Soyza, Anthony; Elborn, J. Stuart; Goeminne, Pieter; Hill, Adam T.; Menendez, Rosario; Polverino, Eva
Abstract: Background: An Expert Forum was held at the 2014 European Respiratory Society International Congress to address issues involved in the management of Pseudomonas aeruginosa infection in patients with non-cystic fibrosis bronchiectasis (NCFB). Multiple studies have found that chronic P. aeruginosa infection is associated with more severe disease and higher morbidity and mortality. Overview: Participants discussed appropriate management of P. aeruginosa infection at three stages: 1) first isolation, including eradication protocols; 2) during exacerbations; and 3) during chronic infection, including long-term antibiotic therapy to reduce the severity of symptoms and frequency of exacerbations. Topics covered included frequency of sputum cultures, antibiotic treatment at first isolation and for exacerbations, optimal use of inhaled antibiotics, indications for long-term therapy, and treatment regimens that may reduce the frequency or severity of symptoms. Electronic polling and roundtable discussions followed by expert insights were used to address these topics. Significant diversity in management practices was reported among different countries and centres, and in many cases clinical management was at variance with published guidelines. Conclusions: This Expert Forum identified standardised terminology, clinician training, additional research into management strategies, and the development of new drugs as areas requiring improvement for the optimal management of P. aeruginosa in NCFB. Highlights: Pseudomonas aeruginosa is linked to severe disease, worse quality of life and higher mortality. Robust evidence for optimal treatment of P. aeruginosa infection in NCFB is lacking. The importance and feasibility of P. aeruginosa eradication is not yet understood. Potential therapies for chronic P. aeruginosa infection are in development.